Development and validation of a gas chromatography method for the simultaneous determination of multicomponents during monoglyceride synthesis by glycerolysis of methyl oleate: Application to homogeneous and heterogeneous catalysis - Ferretti, Cristián Alejandro (2011)
A gas chromatography (GC) method for the simultaneous determination of glycerol, methyl oleate, monoglycerides (alpha- and beta-glyceryl monooleates), diglycerides (1,2- and 1,3-glyceryl dioleates), and triglycerides is postulated and validated to monitor the reaction product evolution during the catalytic synthesis of monoglycerides by glycerolysis of methyl oleate. The method is suitable for quantitative analysis of the multiphase reaction system, either under liquid or solid catalyzed conditions in a wide concentration range. Excellent separation of all the analytes was achieved with a 15 m-capillary column of 100% methyl polysiloxane in 35 minutes. A discussion on different solvents (toluene and n-hexane) and derivatization procedures is presented. A proper and unique combination of silylating agents for the trimethylsilylation of the free hydroxyl groups of glycerol, mono- and diglycerides is proposed as well as two internal standards, n-hexadecane and cholesterol. The method accuracy was evaluated from recovery experiments and the precision by repeated analysis of each sample. Relative recoveries of the analytes ranged from 98-105 % and relative standard deviations from 4.8 to 13.0 %. Good linearity of calibration curves was obtained in the investigated concentration ranges with high correlation coefficients (r2 > 0.996) for all the analytes.